2000
DOI: 10.2165/00063030-200013010-00006
|View full text |Cite
|
Sign up to set email alerts
|

Prospects for a Vaccine in Allergic Diseases and Asthma

Abstract: Allergen-specific immunotherapy is widely used to treat allergic diseases, and current research is now focusing on the development of therapeutic vaccines acting on the IgE immune response following allergen challenge. The IgE immune response is dependent on genetic and environmental factors; production of IgE results from complex interactions among B cells, T cells, mast cells, basophils,surface and adhesion molecules and various cytokines. New vaccination methods under investigation involve allergen-specific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2014
2014
2014
2014

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 123 publications
0
1
0
Order By: Relevance
“…Activated mast cells appear to be the primary effector cell in the pathogenesis of atopic asthma. It has been previously reported that cellular infiltrate in bronchial biopsies and bronchoalveolar lavage of asthmatic patients contains several inflammatory cells, including mast cells (27), eosinophils, and T helper 2 (Th2) lymphocytes generating interleukin-3 (IL-3), IL-4, IL-5, IL-9, IL-13, and granulocyte macrophage colony-stimulating factor (GM-CSF) (28)(29).…”
mentioning
confidence: 99%
“…Activated mast cells appear to be the primary effector cell in the pathogenesis of atopic asthma. It has been previously reported that cellular infiltrate in bronchial biopsies and bronchoalveolar lavage of asthmatic patients contains several inflammatory cells, including mast cells (27), eosinophils, and T helper 2 (Th2) lymphocytes generating interleukin-3 (IL-3), IL-4, IL-5, IL-9, IL-13, and granulocyte macrophage colony-stimulating factor (GM-CSF) (28)(29).…”
mentioning
confidence: 99%